Corps, couleur et sexualité : plaçage et quarteronnes à la Nouvelle-Orléans au xixe siècle - Nathalie Dessens (Les Cahiers de Framespa)
In plantation societies of the Americas, body and slavery have always been intricately linked. The slave’s body was always in full view, whether in the fields or at the auction block. It was sometimes the slave’s identity card, in the fugitive slave notices masters published in the newspapers. It was always a symbol of sexuality, exoticism, and sin. The question of the representation of the body in slave societies offers an unlimited source of discussion. The present article is a case study of the construction of a myth, that of plaçage in New Orleans. Through a historiographical discussion, it examines the construction of the myth, its origins, and analyses what the perception and representation of the body in slave societies reveal.